C.T.R. Hayward. Interpretations of the Name Israel in Ancient Judaism and Some Early Christian Writings: From Victorious Athlete to Heavenly Champion - Tyson, Joseph B. (Studies in Christian-Jewish Relations, 2011)
No abstract is available.